S211. LONG-TERM BENZODIAZEPINE USE DURING MAINTENANCE THERAPY OF PSYCHOSIS - ASSOCIATION WITH SYMPTOMS, COGNITION AND FUNCTIONALITY. (18th May 2020) - Maric, Nadja; Andric Petrovic, Sanja; Ristic, Ivan; Jerotic, Stefan; Savic, Bojana; Zebic, Mirjana; Vukovic, Vuk; Voskresenski, Tatjana; Jovanovic, Nikolina
Abstract: Background: Data on benzodiazepine (BZD) use of on a long term basis (≥6 months) in outpatients with psychosis spectrum disorders (PSD) are scarce. However, prolonged BZD administration could be associated with different side effects, thus its use in actual practice must be described and questioned. According to the recent large-scale study of hospital discharge BZD prescription in Balkans, PSD patients had higher odds of receiving BZDs (80.4%) in comparison to patients with all other main ICD-10 psychiatric categories. This study explored the prevalence of long-term BZD use during maintenance therapy of patients with PSD and the associated clinical factors. Methods: Outpatients with primary diagnosis of psychosis or related disorder (ICD-10 F20-29), history of at least one lifetime psychiatric hospital admission, capacity and will to provide informed consent and a history of attending the outpatient clinic for at least 6 months were included from two sites in Serbia - one university and one general psychiatric hospital (n=60; mean age (SD) = 43.4 (10.6) years; 63.3% male). Clinical assessment included Brief Psychiatric Rating Scale (BPRS, mean (SD) = 1.73 (0.49)), the split version of General Assessment of Functioning scale (GAF Functioning/Symptom, mean (SD) = 58.5 (11.7) and 58.6 (11.7), respectively), Global Assessment of Functioning - Cognition in Schizophrenia (GAF-CogS, mean (SD) = 60.4 (12.4)) and Recovering Quality of Life (ReQoL, mean (SD) = 29.0 (9.1)). Medical chart review was used to list all psychotropic medications prescribed over 6 months preceding the examination. We used student t-test and Pearson's correlation to analyze the data. Effect sizes were provided. Present research was conducted as a part of the larger study aiming at implementation of the psychosocial intervention DIALOG+ for patients with psychotic disorders in low- and middle-income countries in South Eastern Europe (grant agreement No 779334). Results: The prevalence of long term BZD use was 50.0% (30/60 patients). The mean BZD daily dose range was 0–14 mg of lorazepam equivalents (21.7% with ≥ 3mg of lorazepm equivalents). Total antipsychotic (AP) daily doses (chlorpromazine equivalents) at the time of evaluation were 371.6±191.4 mg in long-term BZD users and 275.0±214.7 mg in the other group (df=56, t= 1, 811, p=0.075, Cohen's d=0.5). The correlation between AP polypharmacy and long-term BZD use was positive (r=0.340, p=0.008). Long term BZD users were borderline older than non-users (df=58, t=1, 957, p=0.055, Cohen's d=0.5) and had higher total BPRS symptom scores (df=58, t= 2, 806, p=0.007, Cohen's d=0.7). In particular, higher symptom scores were noticed in two BPRS domains - negative symptom and reality distortion. Moreover, these patients were significantly more likely to have cognitive and functional impairments (GAF-CogS: df=56, t=-3.295, p=0.002, Cohen's d=0.9; GAF-F: df=56, t=-3, 186, p=0.002, Cohen's d=0.8; GAF-S: df=56, t=-3, 316, p=0.002, Cohen's d=0.9). There were no between-group differences in ReQoL scores (df=58, t=-1.563, p=0.123). Discussion: The present study demonstrated new information regarding the prescription patterns of BZD in outpatients with PSD in Serbia, amplified with clinically relevant information. High rate of long term BZD prescription could be considered as a therapeutic strategy toward patients with more severe cases of PSD, however our results could also suggest a link between long-term BZD prescription and disabling side effects, particularly related to cognitive functioning. Overall, this is an under-researched area and present findings are likely to contribute to improving clinical practice and care for patients with psychotic disorders.